Temperature dependent fracture initiation in microscale silicon. (15th March 2017) - Hintsala, Eric D.; Bhowmick, Sanjit; Yueyue, Xie; Ballarini, Roberto; Asif, S. A. Syed; Gerberich, William W.
Abstract: We present novel in-situ scanning electron microscope experiments exploring the fracture of silicon as a function of temperature at the microscale, from room temperature to 600 °C. Clear post mortem TEM observations of dislocation activity at and above 450 °C suggest that back stresses from crack-tip dislocation emission raise the applied stress intensity at initiation, as part of a brittle to ductile transition starting at 300 °C. This is in agreement with other microscale measurements; however, these experiments are particularly noteworthy in their ability to directly observe crack advance and perform post-mortem analysis to investigate dislocation activity. Graphical abstract: